Development of Web-Based Interactive Learning Media as A Digital Innovation in Hardware and Software Materials at SMP Negeri 1 Senori - Muhammad Rinov Cuhanazriansyah; Day Ramadhani Amir; Dewi Anisa Hidayanti (JURNAL PTI (PENDIDIKAN DAN TEKNOLOGI INFORMASI) FAKULTAS KEGURUAN ILMU PENDIDIKAN UNIVERSITA PUTRA INDONESIA "YPTK" PADANG, 2026)
The rapid development of digital technology has encouraged schools to integrate innovative learning media into classroom instruction. However, the learning process of Information and Communication Technology (ICT) at SMP Negeri 1 Senori still relies on conventional teaching methods, such as lectures and PowerPoint presentations, which limit students' engagement and conceptual understanding of computer hardware and software. This study aimed to develop an interactive web-based learning media and evaluate its validity, practicality, and effectiveness in improving students' conceptual understanding and learning motivation. The research employed the Research and Development (R&D) approach using the ADDIE model, consisting of Analysis, Design, Development, Implementation, and Evaluation stages. The developed product integrates multimedia components, including text, images, videos, animations, and interactive quizzes within a web-based platform accessible through computers and mobile devices. Product quality was evaluated by media experts and subject matter experts, while practicality was assessed through teacher and student responses. Effectiveness was determined using pre-test and post-test scores as well as students' learning motivation questionnaires. The findings indicate that the developed learning media fulfills the criteria of valid, practical, and effective instructional media. Furthermore, the integration of multimedia and interactive features facilitates active learning, enhances conceptual understanding of computer hardware and software, and increases students' motivation during classroom instruction. Therefore, the proposed web-based learning media can serve as an effective digital learning resource for ICT learning at the junior high school level.